When Pinocchio's nose does not grow: belief regarding lie-detectability modulates production of deception - Sip, Kamila E.; Carmel, David; Marchant, Jennifer L.; Li, Jian; Petrovic, Predrag; Roepstorff, Andreas; McGregor, William B.; Frith, Christopher D. (Frontiers in Human Neuroscience, 2013)
Does the brain activity underlying the production of deception differ depending on whether or not one believes their deception can be detected? To address this question, we had participants commit a mock theft in a laboratory setting, and then interrogated them while they underwent functional MRI (fMRI) scanning. Crucially, during some parts of the interrogation participants believed a lie detector was activated, whereas in other parts they were told it was switched off. We were thus able to examine the neural activity associated with the contrast between producing true versus false claims, as well as the independent contrast between believing that deception could and could not be detected. We found increased activation in the right amygdala and inferior frontal gyrus (IFG), as well as the left posterior cingulate cortex (PCC), during the production of false (compared to true) claims. Importantly, there was a significant interaction between the effects of deception and belief in the left temporal pole and right hippocampus/parahippocampal gyrus, where activity increased during the production of deception when participants believed their false claims could be detected, but not when they believed the lie detector was switched off. As these regions are associated with binding socially complex perceptual input and memory retrieval, we conclude that producing deceptive behavior in a context in which one believes this deception can be detected is associated with a cognitively taxing effort to reconcile contradictions between one’s actions and recollections.